Assessment of basal heave using slip circle method - Lay, Yandi Layadi (2015)
The scarcity of land space in many cities has increased interest in the use of underground space, which in turn renders braced excavation more important and highly demanded. To ensure the stability of the excavation, it is necessary to calculate the factor of safety against basal heave. Conventional methods such as Terzaghi’s method and Bjerrum & Eide’s method have been used for a long time. There have been studies directed towards improvement of those methods. Another approach to basal heave stability problem is by using the slip circle method. Although the method is widely used in Japan and Taiwan, thorough understanding on the performance of this method is not yet well established. Thus, this study is aimed to assess the performance of the slip circle method through comparative studies based on the results from finite element method (PLAXIS 2D) and the conventional Terzaghi’s method. A series of parametric studies have been carried out on five key parameters.The results showed that the factor of safety computed from the slip circle method is governed by the undrained shear strength of the clay (cu) and the depth of wall penetration below the excavation base (D). The slip circle method does not consider the other three important parameters that influence the basal heave stability: width of excavation (B), clay thickness beneath bottom of excavation (T), and wall stiffness (EI). The results also indicated that the slip circle method yields an overly conservative factor of safety relative to the results from PLAXIS 2D. Despite its drawback, the method can still be useful in determining the ideal depth of wall penetration by setting the factor of safety equal to at least 1.2, as suggested by some building codes. The results also suggested that the condition D/H ≥ 1 and D/T ≥ 0.5 should be satisfied for the depth of wall penetration (D) below excavation base in order to achieve a significant improvement when replacing a sheet pile wall with a diaphragm wall.